O valor prognóstico da cinética do ritmo de filtração glomerular estimado e sua relação com escore de gravidade de lesão renal aguda em pacientes críticos em UTI - Marques, Flávio de Oliveira (2018)
Although advances have been achieved in acute kidney injury (AKI) research following this classification, potential pitfalls can be identified in clinical practice. Recently, the kinetic estimated glomerular filtration rate (KeGFR) has been advocated in AKI assessment. The aim of this study was to compare and evaluate the KeGFR model to AKI severity scores and its role in add prognostic information in critically-ill patients in ICU. This study was a retrospective cohort using data from the Multiparameter Intelligent Monitoring in Intensive Care II (MIMIC-II) project that contains data on patients hospitalized in ICU at Beth Israel Deaconess Center from 2001 to 2008. The KeGFR was calculated during the first 7 days of ICU stay in 13,284 patients and correlated with outcomes such as the need for renal replacement therapy (RRT), hospital mortality and survival up to 1 year. In general, there was not a good agreement between AKI severity and the worst achieved KeGFR. The stepwise reduction in the worst achieved KeGFR conferred an incremental mortality, rising from 7.0% (KeGFR>70ml/min/1.73 m2) to 27.8% (KeGFR<30ml/min/1.73 m2). Patients with AKI stage 3 who maintained KeGFR >70ml/min/1,73 m2 had a mortality rate of 16.5%, close to those patients with KeGFR <30ml/min/1.73 m2 but no AKI; additionally, mortality increased to 40% when both AKI stage 3 and KeGFR <30ml/min/1.73 m2 were present. In relation to another outcome, the need for RRT, patients with worst achieved KeGFR<30ml/min/1.73 m2 and KDIGO stage 1/2, the rate of RRT was less than 10%. However, this rate was 44% when both AKI stage 3 and a worst KeGFR < 30ml/min/1.73 m2 were observed. This interaction between AKI and KeGFR was also present in long-term survival, being worst when AKI stage 3 and KeGFR< 30ml/min/1,73 m2 were present. In conclusion, both the AKI classification system and KeGFR are complimentary to each one. Assessing both AKI stage and KeGFR can help to identify patients at different AKI risk levels in clinical practice.